Efeito da natação e do basquetebol em cadeira de rodas sobre o colesterol HDL: uma investigação em indivíduos com lesão medular - Rodrigues, Fábio Barreto (2007)
Despite the observation of an increase in life expectancy in individuals with Spinal cord injury (SCI), it is lower than that of the general population. Studies have shown that affected individuals have a sedentary lifestyle that reflects negatively on health and quality of life. Studies have demonstrated that HDL cholesterol (HDL-C) levels, a high-density lipoprotein and important predictor of cardiovascular disease, are lower in this population exposing these people to a greater incidence of heart disease from atherosclerotic process In the general population, exercise increases HDL-C serum levels, but this phenomenon is not very clear in people with spinal cord injury (SCI). The present study examined the effect of both swimming and wheelchair basketball in the lipid profile of eleven men and seven women with SCI. The subjects included in regular exercise programs showed increases in HDL-C levels and decreases in CT/HDL-C and LDL-C/HDL-C ratios. We found better results mainly in men with lower levels of SCI and in those that sustained exercise intensities above 60% of the heart rate reserve. The duration of training sessions can be an essential factor in these results. The results suggest that both the exercise prescription and the personal characteristics of people with SCI influence changes in the lipid profile mediated through exercise. The elaboration of this work is an attempt to clarify uncertainties about health and the longevity of people with SCI generated in discussion of all members of the interdisciplinary rehabilitation team, especially the physiotherapists, nutritionists, nurses and physicians that contributed considerably in all phases of the research